How Will Disenfranchised Peoples Adapt to Climate Change? Strengthening the Ecojustice Movement - Klenk, Nicole Lisa; Bazely, Dawn; Perkins, Patricia E. (Ellie) (IRIS, York University, 2010)
The fourth assessment of the Intergovernmental Panel on Climate Change (IPCC) acknowledged that millions of people are currently, and will increasingly be, affected by the impacts of climate change, in the form of floods, droughts and other extreme events, as well as related threats to food security. In response to these global environmental changes, the international community, including civil society, is acting on the need for immediate adaptation measures and is developing strategies for future adaptation. However, the impacts of climate change are unevenly distributed, with many of the poorest, most vulnerable peoples experiencing the immediate effects of climate change, in the here and now. As the IPCC noted, developing countries are disproportionately affected by climate change and often, the least able to adapt due to lack of infrastructure and resources. The first, of what we hope will be many Ecojustice-themed Conferences, was held at York University in 2009. The idea for the conference came out of a conversation that York University’s Sheila Embleton (Vice-President Academic) and Adrian Shubert (Associate Vice-President International) had, on a trip to South America, with Miriam Duailibi, Director of the ECOAR Institute for Citizenship in Brazil, an NGO formed after the 1992 Earth Summit. Miriam expressed her frustration at how many conferences on climate change tend to feature academics and others from the Global North lecturing the Global South about how to respond to climate change. Miriam challenged York University to hold a different kind of conference, at which the Global North would be the audience, hearing about the circumstances, needs and realities of people in developing countries as well as how local peoples are responding to these challenges. A steering committee was formed in Fall 2008, and the scope of the conference was broadened to include voices from South Africa and India. Most significantly, the First Nations and Inuit presented the Canadian viewpoint. The conference brought ...